ROLE OF MgSO4 IN NEURO PROTECTION IN PATIENTS PRESENTING WITH PRETERM LABOUR BETWEEN 28 TO 32 WEEKS - IFTIKHAR , A; SADAF , R (Biological and Clinical Sciences Research Journal, 2024)
Preterm birth (PTB) is a major contributor to neonatal morbidity and mortality, with significant neurological complications, including cerebral palsy and developmental delays. Magnesium sulfate (MgSO₄) has been proposed as a neuroprotective agent for preterm neonates, but its efficacy requires further evaluation in clinical settings. Objectives: To determine the role of MgSO4 in neuroprotection in patients presenting with preterm labor between 28 to 32 weeks of gestation. Methods: This study commenced after obtaining approval from the hospital's ethical board and research committee. Eligible patients who provided written informed consent were recruited from inpatient and outpatient departments. The study's purpose and benefits were explained to participants, ensuring confidentiality and clarifying that participation would not affect future medical care. Demographic and baseline data were documented, including age, gestational age, parity, BMI, residence, and comorbidities. Blocked randomization was used to allocate patients equally to Group A or Group B. Group A received MgSO₄ starting with a 4 g intravenous infusion over 20 minutes, followed by a maintenance dose of 1 g per hour via infusion pump until delivery. Group B received a placebo. Deliveries were conducted in the labor unit following hospital protocols for high-risk pregnancies, with instrumental assistance or cesarean sections performed as needed under the guidance of a consultant gynecologist. Newborns were transferred to the neonatal intensive care unit and observed for 48 hours for seizures, based on operational definitions. Data were collected by the researcher using a structured proforma. Data was analyzed using SPSS version 25. Results: The study involved 154 participants with a mean age of 32.62. Group A showed significantly higher neuroprotection (94.8%) than Group B (79.2%), with a p-value of 0.004. Factors like age, gestation, parity, and comorbidities had no significant impact on outcomes in either group. Conclusion: MgSO4 effectively reduces neurological risks in preterm neonates, emphasizing timely use, safety, and feasibility in standard care, with further research needed for validation.